Speech Language Disorder in Children: An Overview - Banu, Laila Areju Man; Saad, Tania; Hossain , Md Kawsar; Hossain, Md Azizul (Journal of Comilla Medical College Teachers’ Association, 2024)
The speech and language development of a child reflects his or her overall growth and cognitive abilities. Children frequently experience speech and language disorders, which may have long-term effects. Depending on its intensity, it could impair daily functioning, communication, learning, and social interaction. The purpose of this review is to address common speech and language disorders, their etiologies, and interventional strategy. With the rising incidence of speech language problem in children, it is important to early identification of the problem that may help us to take appropriate measures. Children's speech and language abilities can be significantly improved with early detection and timely intervention. J Com Med Col Teachers’ Asso July 2023; 27(2): 75-82